The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1113/jphysiol.2004.076307
|View full text |Cite
|
Sign up to set email alerts
|

Human postural sway results from frequent, ballistic bias impulses by soleus and gastrocnemius

Abstract: It has been widely assumed for nearly a century, that postural muscles operate in a spring-like manner and that muscle length signals joint angle (the mechano-reflex mechanism). Here we employ automated analysis of ultrasound images to resolve calf muscle (soleus and gastrocnemius) length changes as small as 10 µm in standing subjects. Previously, we have used balancing of a real inverted pendulum to make predictions about human standing. Here we test and confirm these predictions on 10 subjects standing quiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
269
0
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(299 citation statements)
references
References 53 publications
19
269
0
10
Order By: Relevance
“…This observation partly coincides with results by Loram et al, showing that changes in the gastrocnemius EMG activity only partially correspond to the observed movements of the body center of mass (CoM) (Loram et al 2005). However, further research is needed to investigate the respective roles of the tibialis anterior and gastrocnemius muscles in human postural control.…”
Section: Effect Of Foam Support Surface and Emg Responsessupporting
confidence: 88%
“…This observation partly coincides with results by Loram et al, showing that changes in the gastrocnemius EMG activity only partially correspond to the observed movements of the body center of mass (CoM) (Loram et al 2005). However, further research is needed to investigate the respective roles of the tibialis anterior and gastrocnemius muscles in human postural control.…”
Section: Effect Of Foam Support Surface and Emg Responsessupporting
confidence: 88%
“…Electromyography studies revealed changes in the ankle joint during quiet standing [8,11], gait and running [12,13]. These are important findings since standing sway is highly correlated with ankle joint rotation, as muscles crossing this joint are able to provide the sensory information required to maintain upright standing [14,15].…”
Section: Introductionmentioning
confidence: 94%
“…Using ultrasound it is possible to non-invasively measure small fluctuations in the changes in length of individual muscle fibers in the calf muscles of a person quietly standing with eyes closed [54,55]. The changes in length reflect changes in the corrective forces made to maintain balance.…”
Section: Introductionmentioning
confidence: 99%